A systemic model for measuring the effectiveness of virtual learning programs. (2015) - Fayyoumi, Ayham; Elia, Gianluca
Although many universities and corporations invest on relevant resources in virtual learning programs, methods and tools for evaluating their success have not been consolidated. This article conducts an extensive literature review and identifies the measures of effectiveness of virtual learning programs and their influencing factors. The key contribution of this study is the proposed systemic model that can be operationally used to measure the effectiveness of virtual learning programs. The model identifies the determinants of effectiveness, namely, 'learner performance' and 'learner satisfaction and confidence', and the factors that influence significantly them. The model has been cross-checked by a panel of field experts and validated through factor and regression analyses involving a sample of university students. Lastly, the model is operationalised using a tool that guides HR managers and practitioners in assessing the effectiveness of their virtual learning programs.